2006
DOI: 10.1007/s00203-005-0081-5
|View full text |Cite
|
Sign up to set email alerts
|

Pelotomaculum terephthalicum sp. nov. and Pelotomaculum isophthalicum sp. nov.: two anaerobic bacteria that degrade phthalate isomers in syntrophic association with hydrogenotrophic methanogens

Abstract: An anaerobic phthalate isomer-degrading strain (JT(T)) that we previously isolated was characterized. In addition, a strictly anaerobic, mesophilic, syntrophic phthalate isomer-degrading bacterium, designated strain JI(T), was isolated and characterized in this study. Both were non-motile rods that formed spores. In both strains, the optimal growth was observed at temperatures around 37 degrees C and neutral pH. In syntrophic co-culture with the hydrogenotrophic methanogen Methanospirillum hungatei, both strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 24 publications
3
72
0
Order By: Relevance
“…Several studies (Chan, 2000;Qiu et al, 2006;Imachi et al, 2008) have observed the existence of multiple bacterial populations in highly enriched methanogenic cultures degrading carbon substrates like formate, acetate, propionate and phthalate isomers. These observations were shown through a defined mixed culture (Dolfing et al, 2008), suggesting that syntrophic interactions in methanogenic enrichments are more complex than simple pairwise syntroph-methanogen relationships.…”
Section: Methanogenic Syntrophymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies (Chan, 2000;Qiu et al, 2006;Imachi et al, 2008) have observed the existence of multiple bacterial populations in highly enriched methanogenic cultures degrading carbon substrates like formate, acetate, propionate and phthalate isomers. These observations were shown through a defined mixed culture (Dolfing et al, 2008), suggesting that syntrophic interactions in methanogenic enrichments are more complex than simple pairwise syntroph-methanogen relationships.…”
Section: Methanogenic Syntrophymentioning
confidence: 99%
“…The syntrophic bacteria, however, are difficult to identify based on phylogenetic classification, and extremely difficult to obtain in pure culture. In the last decade, only three bacterial species that can degrade TA and its isomers have been successfully co-cultured with methanogens under mesophilic conditions (Qiu et al, 2006(Qiu et al, , 2008, and these isolates are different from those found under thermophilic conditions (Chen et al, 2004). This greatly limits the effort to understand the microbial interaction and function in the TA-degrading consortia.…”
mentioning
confidence: 99%
“…Pelotomaculum and Syntrophorhabdus are known to syntrophically metabolize TA (Wu et al, 2001;Qiu et al, 2004Qiu et al, , 2006Qiu et al, , 2008. In this reactor specifically, Pelotomaculum syntrophically interacts with methanogens and predominates TA degradation (Chen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This was possibly due to the characteristic feature of the corresponding organism, namely dependence on complex interactions established in the microbial community. Actually, the studies on Pelotomaculum, the genus known for its ability to degrade propionate, have shown that cultivation of this group of bacteria is difficult even under coculture with a specific archaeal strain (de Bok et al, 2005;Imachi et al, 2002;Qiu et al, 2006). Hence, we assumed that development of an appropriate mixed (commensal) culture condition may be useful to stably maintain propionate-degrading microorganisms and their activity.…”
mentioning
confidence: 99%
“…The bacterium corresponding to EPE306 (band f ) was a member of Pelotomaculum, the genus known for its involvement in propionate metabolism (de Bok et al, 2005;Imachi et al, 2002;Qiu et al, 2006). The 16S rRNA gene sequences almost identical to that of EPE306 have been obtained in propionate-degrading enrichments ) and a thermophilic packed-bed bioreactor degrading garbage (Sasaki et al, 2007), although the corresponding bacterium has not yet been isolated.…”
mentioning
confidence: 99%